2002
DOI: 10.1073/pnas.012682399
|View full text |Cite
|
Sign up to set email alerts
|

A pervasive mechanism for analgesia: Activation of GIRK2 channels

Abstract: G protein-coupled inwardly rectifying potassium channels (GIRKs) provide a common link between numerous neurotransmitter receptors and the regulation of synaptic transmission. We asked whether GIRKs specify a single behavioral action that is produced by drugs acting on the diverse receptors coupled with GIRKs. By using GIRK2-null mutant mice, we found marked reduction or complete elimination of the antinociceptive (hot plate test) effects of ethanol, oxotremorine, nicotine, baclofen, clonidine, and the cannabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 40 publications
6
116
0
2
Order By: Relevance
“…Studies using GIRK2-deficient mice and weaver mutant mice, which have mutant GIRK2 channels insensitive to G proteins and ethanol, have shown that the analgesic effects induced by opioids or ethanol are remarkably reduced in these mice, suggesting that the GIRK channel activation induces analgesia (Kobayashi et al, 1999;Ikeda et al, 2000Ikeda et al, , 2002Blednov et al, 2003;Mitrovic et al, 2003). However, our studies have demonstrated that various tricyclic antidepressants and fluoxetine inhibit GIRK channels.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Studies using GIRK2-deficient mice and weaver mutant mice, which have mutant GIRK2 channels insensitive to G proteins and ethanol, have shown that the analgesic effects induced by opioids or ethanol are remarkably reduced in these mice, suggesting that the GIRK channel activation induces analgesia (Kobayashi et al, 1999;Ikeda et al, 2000Ikeda et al, , 2002Blednov et al, 2003;Mitrovic et al, 2003). However, our studies have demonstrated that various tricyclic antidepressants and fluoxetine inhibit GIRK channels.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies using GIRK2-deficient mice suggested that GIRK activators may be useful for the treatment of epilepsy and pain (Signorini et al, 1997;Ikeda et al, 2002;Blednov et al, 2003). In addition, since GIRK knockout mice show decreased cocaine self-administration (Morgan et al, 2003), selective GIRK channel inhibitors might be potential agents for the treatment of abusers of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol modulation of GIRK channels regulates neuronal excitability in the brain's reward circuit (11) and underlies forms of alcohol addiction (6,(8)(9)(10)36). Here, we uncovered previously undescribed principles governing alcohol modulation of GIRK channels.…”
Section: Discussionmentioning
confidence: 87%
“…Studies involving mice with mutant Girk genes have implicated GIRK channels in nociception and the acute analgesic effect of morphine (Ikeda et al, 2000;Blednov et al, 2003;Mitrovic et al, 2003;Marker et al, 2004Marker et al, , 2006. For example, weaver mice, which harbor a mutation in the Girk2 gene, exhibited blunted responses to systemic morphine analgesia as measured by the hot-plate test (Ikeda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%